Role of Tri-Phasic Computed Tomography in Evaluation of Hepatocellular Carcinoma Patients with Liver Cirrhosis - Naila Tamkeen; Wahid, Ghazala; Adnan Ahmad; Samad, Mehreen; Rehman, Mahnoor; Khushbakht; Afsar, Maimoona (Journal of Gandhara Medical and Dental Science, 2022)
OBJECTIVES To assess the usefulness of Tri-phasic computed tomography in the evaluation of hepatocellular carcinoma in cirrhotic patients. METHODOLOGY This cross-sectional study was carried out in the Radiology and Imaging Department of Hayatabad Medical Complex Peshawar from October 2020 to September 2021 (01 year). Tri-phasic CT was done in all patients. Patients with suspected hepatocellular carcinoma diagnosed by clinical and ultrasonography and having high serum α-fetoprotein levels were enrolled in the study. RESULTS Malignant cases on tri-phasic CT were 120(82.8%) while benign cases were 25 (17.2%) Fig -I. In malignant tumor cases, 99(82.5%) patients had hepatocellular carcinoma (HCC), 13(10.8%) had metastases and 8(6.7%) had dysplastic nodule respectively. In benign tumour cases, 15(60%) had regenerative nodules, 6(24%) had hepatic adenoma and 4 (16%) had haemangioma. Tri -phasic CT as a tool in the diagnosis of hepatocellular carcinoma in cirrhotic patients showed a sensitivity of 96.8%, specificity of 79.7%, the accuracy of 95%, positive predictive values of 96.2% and negative predictive values of 88.1%. CONCLUSION Tri-Phasic CT can be an ideal diagnostic tool for detecting as well as characterizing hepatocellular carcinoma in cirrhotic patients.